Attitude and Influence of Teachers towards Information and Communication Technology: Exploring the Impact of ICT on Teacher Attitudes and Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
ICT has been a part of our lives for the past few decades, impacting both our culture and our private lives. ICT that is still commonly used in the field of education. Teacher, Teacher, Administrator and other citizens interested with schooling are popularly using ICT. The learning method was highly affected by rapid developments in information communication technology (ICT). This paper addressed the attitude of teachers towards information communication technology with variables that affect the attitudes of teachers and the role of ICT in 21st century teacher education.